Academic entrepreneurship university spinoffs and wealth creation - Shane, Scott Andrew 1964- (Edward Elgar, 2004)
1. Introduction -- 2. Why do university spinoffs matter? -- 3. University spinoffs in historical perspective -- 4. Variation in spinoff activities across institutions -- 5. Environmental influences on spinoff activity -- 6. The types of technology that lead to university spinoffs -- 7. The industries where spinoffs occur -- 8. The role of people in university spinoffs -- 9. The process of spinoff company creation -- 10. The process of spinoff development -- 11. The financing of university spinoffs -- 12. The performance of university spinoffs -- 13. The problems with university spinoffs -- 14. Conclusions
Includes bibliographical references and index
Keywords: Electronic books; High technology industries -- United States; University-based new business enterprises -- United States; Academic-industrial collaboration -- United States; Research, Industrial -- United States; Technology transfer -- United States; Entrepreneurship -- United States